Association between adiponectin concentration and metabolic syndrome in individuals attending health check-ups at Hue Central Hospital - Huong, Hoang Thi Lan; Dang, Tran Huu; Chi, Le Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: adiponectin, secreted by adipose tissue, is involved in the regulation of body weight. Dysregulation of adiponectin is associated with obesity, metabolic syndrome. Methods: A cross-sectional study was conducted on 206 individuals aged over 18 years undergoing health check-ups at Hue Central Hospital from October 2025 to February 2026. Multivariate linear regression analysis was performed to evaluate the associations between adiponectin levels and study variables. Receiver operating characteristic (ROC) curve analysis was used to assess the discriminatory value of adiponectin for metabolic syndrome. Results: The median serum adiponectin level was 7.64 (5.11–12.87). Serum adiponectin levels were significantly higher in females than in males [9.58 (6.26–13.94) vs. 5.59 (3.88–8.21), respectively; p < 0.001]. Multivariate linear regression analysis demonstrated that age, sex, BMI, and metabolic syndrome were independently associated with adiponectin levels. At a cut-off value of ≤ 5.26, adiponectin yielded a sensitivity of 40.5%, a specificity of 81.1%, and an AUC of 0.616 (p = 0.004) for metabolic syndrome. Conclusion: Serum adiponectin levels were associated with components of metabolic syndrome in individuals undergoing health check-ups at Hue Central Hospital. Adiponectin levels were independently associated with age, sex, BMI, and metabolic syndrome.